On the Static and Dynamic Behavior of a Prehistoric Structure Typical of Apulia in Italy. (2017) - Venerito, M.; Foti, D.; Vitti, M.
Abstract: This paper examines the structural behavior to vertical and horizontal loads (static equivalent by horizontal forces) of a structure typical of Apulia, in Italy. The structure is in masonry and is called " trullo ". It is very famous and is found only in Apulia. This structure, in fact, known as one of the "wonders of the world", was built in the prehistoric age and therefore it has not been realized by mean of a structural design, but only thanks to the experience of "master" builders. By mean of a linear static analysis and having previously calculated the horizontal load, it has been possible to demonstrate the good resistance of this structure to earthquakes. The results will give more information of the behavior of Trulli and if they need any retrofitting to dynamic loads. Knowing the characteristics of this structure that make it resistant to the most severe actions, it will be possible to use them for future buildings. A structure of the past will become then a starting point for constructions of the future. Finally, this research should give directions to the definition of sustainable methodologies that could be able to classify and control old structures and perhaps prevent their collapse, giving information on which interventions of consolidation are to be adopted.